Perovskite solar cell and preparation method thereof

By introducing a protective film between the insulating layer of perovskite solar cells and the carbon electrode, the problem of device short circuit is solved, and the electrochemical performance and photoelectric conversion efficiency are significantly improved, which is suitable for large-area battery production.

CN119855450AActive Publication Date: 2025-04-18HUADIAN ELECTRIC POWER SCI INST CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411996777.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-18
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In the preparation process of three-layer mesoporous carbon electrode perovskite solar cells, short circuits of blank devices are often encountered, resulting in a decrease in the photoelectric conversion efficiency of the battery.

Method used

Using the method of sacrificing protective film, a protective film is temporarily introduced between the insulating layer and the carbon electrode to prevent the infiltration of the carbon slurry from the insulating layer and contact with the electron transport layer, thereby preventing the device from short-circuiting.

Benefits of technology

It effectively prevents the short circuit problem of perovskite solar cells in the three-layer mesoporous carbon electrode, improves the electrochemical performance and photoelectric conversion efficiency of the device, and is suitable for the production of large-area batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224884030000111
    Figure BDA0005224884030000111
  • Figure BDA0005224884030000121
    Figure BDA0005224884030000121
  • Figure HDA0005224884350000011
    Figure HDA0005224884350000011
Patent Text Reader

Abstract

The invention relates to the technical field of new energy materials, in particular to a perovskite solar cell and a preparation method thereof. The preparation method comprises the following steps: A) coating a conductive substrate with electron transport layer slurry, and heating to form an electron transport layer; coating the electron transfer layer with the insulating layer slurry, and heating to form an insulating layer; coating the insulating layer with a protective material, and curing to obtain a protective film; coating a protective film with the carbon slurry, and heating to form a carbon electrode and volatilize the protective film to obtain a blank device; the preparation raw materials of the electron transport layer slurry, the insulating layer slurry and the carbon slurry are limited; b) dropwise adding the perovskite precursor solution to the carbon electrode of the blank device, and after the perovskite precursor solution fully permeates into the carbon electrode, the insulating layer and the electron transport layer, annealing to obtain a perovskite-containing device; and C) covering a back plate, connecting a lead, and smearing a sealant to obtain the mesoporous perovskite solar cell. The short circuit problem of the battery can be effectively prevented, and the electrochemical performance is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a perovskite solar cell and a preparation method thereof. Background Art

[0002] Perovskite solar cells have the advantages of high theoretical conversion efficiency and low cost, and are the next generation of solar cells that have the potential to replace silicon-based solar cells. Mesoporous perovskite solar cells have significant advantages in increasing the contact area between perovskite and charge transport layer (electron transport layer, hole transport layer), increasing carrier separation, and improving the photoelectric conversion efficiency of the cell. The preparation method is to first prepare nano-scale electron transport materials, hole transport materials, insulating layers and other materials into slurry, apply them on the surface of the conductive substrate, remove the solvent to form a porous structure, and then infiltrate the perovskite precursor solution into the porous structure, and promote the crystallization of perovskite by heating and evaporation, etc., to make a mesoporous perovskite solar cell.

[0003] The key to the preparation of mesoporous perovskite solar cells is to make a high-performance slurry. Perovskite solar cell slurry generally uses pineneol as a solvent, ethyl cellulose and lauric acid as a thickener and surfactant, respectively, and is made through mixing, rotary evaporation and other processes (see Nano Lett. 2014, 14, 2, 1000-1004, patent CN202210806436.4, etc.). A representative mesoporous perovskite solar cell technology is a three-layer mesoporous carbon electrode mesoporous perovskite solar cell (see reference J.Phys.Chem.Lett.2014,5,17,2927-2934). This method requires first coating the electron transport layer slurry, the insulating layer slurry, and the carbon slurry on the FTO glass in sequence, heating and calcining to remove the pine alcohol in the slurry, and promoting the decomposition and volatilization of ethyl cellulose to form pores, forming a "blank device" without perovskite, and then dripping the perovskite precursor solution on the blank device and infiltrating it into the porous structure, and then heating and evaporating to induce perovskite crystallization to make a perovskite solar cell. This method does not require a hole transport layer, which greatly reduces the cost. At the same time, the carbon electrode does not react chemically with the perovskite, which improves the stability of the battery.

[0004] However, in the preparation process of three-layer mesoporous carbon electrode perovskite solar cells, the problem of blank device short circuit is often encountered. After the carbon slurry is coated on the insulating layer slurry, due to the strong solubility and permeability of pine oil alcohol in the slurry, the carbon slurry often penetrates the insulating layer and contacts the electron transport layer, causing the device to short-circuit and leak. The reduction of the leakage resistance of the battery device will greatly increase the leakage loss, resulting in a cliff-like drop in the photoelectric conversion efficiency of the device. In previous production practices, most of the methods used are to cool and age the device coated with the insulating layer, and then apply carbon slurry to alleviate the corrosion of the insulating layer by the carbon slurry, but it cannot completely avoid the penetration and short circuit of the carbon electrode to the insulating layer. For the production of large-area batteries, this short circuit problem has a particularly serious impact. Therefore, it is urgent to develop a process that can effectively prevent the corrosion of the insulating layer by the carbon slurry, prevent the carbon electrode from contacting the electron transport layer, and prevent short circuits. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a perovskite solar cell and a preparation method thereof, which can effectively prevent the short circuit problem of the three-layer mesoporous carbon electrode perovskite solar cell, and the obtained perovskite solar cell has better electrochemical performance.

[0006] The present invention provides a method for preparing a perovskite solar cell, comprising the following steps:

[0007] A) coating an electron transport layer slurry on a conductive substrate, heating and annealing to form an electron transport layer; coating an insulating layer slurry on the electron transport layer, drying to form an insulating layer; then coating a protective material on the insulating layer, and curing to obtain a protective film; then coating a carbon slurry on the protective film, heating and annealing to form a carbon electrode and volatilizing the protective film to obtain a blank device without perovskite;

[0008] The raw materials for preparing the electron transport layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an electron transport material; the raw materials for preparing the insulating layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an insulating layer material; the raw materials for preparing the carbon slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and a carbon material;

[0009] B) dropping a perovskite precursor solution onto the carbon electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing to obtain a perovskite-containing device;

[0010] C) Covering the bottom electrode of the device obtained in step B) with a back plate, connecting wires, and applying sealant to obtain a mesoporous perovskite solar cell.

[0011] Preferably, the protective material is selected from at least one of vaseline, paraffin, stearic acid and oleic acid.

[0012] Preferably, the dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; the volume of the dispersant is 1% to 10% of the volume of terpineol;

[0013] The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyethylene glycol; the dosage ratio of the thickener to the terpineol is 50-250 mg: 1 mL;

[0014] The volume of the ethanol is 1 to 3 times the volume of terpineol.

[0015] Preferably, the electron transport material comprises TiO2, SnO2 or ZnO;

[0016] The electron transport material is a nanoparticle with a particle size of 10 to 100 nm;

[0017] In the raw materials for preparing the electron transport layer slurry, the usage ratio of the electron transport material to the pinene alcohol is 50-200 mg:1 mL.

[0018] Preferably, the method for preparing the electron transport layer slurry comprises the following steps:

[0019] Mixing pinene alcohol, a dispersant, a thickener, ethanol and an electron transport material, and removing the ethanol by rotary evaporation to obtain an electron transport layer slurry;

[0020] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 45 to 60° C., and a heating time of 4 to 12 hours.

[0021] Preferably, the insulating layer material includes ZrO2, Al2O3 or SiO2;

[0022] The insulating layer material is nanoparticles with a particle size of 10 to 100 nm;

[0023] In the raw materials for preparing the insulating layer slurry, the usage ratio of the insulating layer material to the pinene alcohol is 150-450 mg:1 mL;

[0024] The method for preparing the insulating layer slurry comprises the following steps:

[0025] Mixing pineol, a dispersant, a thickener, ethanol and an insulating layer material, and removing the ethanol by rotary evaporation to obtain an insulating layer slurry;

[0026] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 45 to 60° C., and a heating time of 4 to 12 hours.

[0027] Preferably, the carbon material is selected from graphite and conductive carbon black;

[0028] The usage ratio of the carbon material to the pine alcohol is 150-450 mg:1 mL;

[0029] The preparation method of the carbon slurry comprises the following steps:

[0030] Mixing terpineol, a dispersant, a thickener, ethanol and a carbon material, and removing the ethanol by rotary evaporation to obtain a carbon slurry;

[0031] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 45 to 60° C., and a heating time of 4 to 12 hours.

[0032] Preferably, the coating thickness of the electron transport layer slurry is 0.5 to 2 μm;

[0033] The coating thickness of the insulating layer slurry is 1 to 3 μm;

[0034] The thickness of the protective film is 0.1 to 10 μm;

[0035] The coating thickness of the carbon slurry is 10 to 50 μm.

[0036] Preferably, in step B), in the perovskite precursor solution, the solvent includes at least one of dimethylformamide and dimethyl sulfoxide; the solute is ABX3; wherein A is at least one of methylamine ion, formamidine ion and cesium ion, and B is Pb 2+ and Sn 2+ At least one of, X is 1 - Br - and Cl - At least one of;

[0037] The concentration of the perovskite precursor solution is 1.0 to 1.5 mol / L;

[0038] The amount of the perovskite precursor solution added to the blank device is 2-4 μL / cm 2 ;

[0039] The annealing temperature is 60-120° C. and the annealing time is 4-24 hours.

[0040] The present invention also provides a perovskite solar cell prepared by the preparation method described above.

[0041] The present invention adopts a sacrificial protective film method to temporarily introduce a protective film between the insulating layer and the carbon electrode. During the coating process, the protective film can block the penetration of the carbon slurry into the insulating layer to prevent the device from short-circuiting. During the subsequent heating and drying process, the protective film volatilizes and does not hinder the penetration of the perovskite precursor solution in the device. The present invention can effectively prevent the short-circuit problem of the three-layer mesoporous carbon electrode perovskite solar cell, and the electrochemical performance of the obtained perovskite solar cell is relatively good, which is of great significance for improving the device yield and producing large-area batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 A comparison diagram of the coating method of the present invention and the conventional perovskite solar cell;

[0043] Figure 2 IV test curves of the mesoporous perovskite solar cells obtained in Examples 1 to 3 of the present invention and the comparative example. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The present invention provides a method for preparing a perovskite solar cell, comprising the following steps:

[0046] A) coating an electron transport layer slurry on a conductive substrate, heating and annealing to form an electron transport layer; coating an insulating layer slurry on the electron transport layer, drying to form an insulating layer; then coating a protective material on the insulating layer, and curing to obtain a protective film; then coating a carbon slurry on the protective film, heating and annealing to form a carbon electrode and volatilizing the protective film to obtain a blank device without perovskite;

[0047] The raw materials for preparing the electron transport layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an electron transport material; the raw materials for preparing the insulating layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an insulating layer material; the raw materials for preparing the carbon slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and a carbon material;

[0048] B) dropping a perovskite precursor solution onto the carbon electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing to obtain a perovskite-containing device;

[0049] C) Covering the bottom electrode of the device obtained in step B) with a back plate, connecting wires, and applying sealant to obtain a mesoporous perovskite solar cell.

[0050] In step A):

[0051] The electron transport layer slurry is coated on the conductive substrate, and heated and annealed to form an electron transport layer; the insulating layer slurry is coated on the electron transport layer, and dried to form an insulating layer; the protective material is then coated on the insulating layer, and cured to obtain a protective film; then the carbon slurry is coated on the protective film, and heated and annealed to form a carbon electrode and volatilize the protective film to obtain a blank device without perovskite;

[0052] The raw materials for preparing the electron transport layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an electron transport material; the raw materials for preparing the insulating layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an insulating layer material; the raw materials for preparing the carbon slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and a carbon material.

[0053] About conductive substrate:

[0054] The conductive substrate includes FTO glass, ITO glass or any other transparent conductive substrate, preferably FTO glass. The film thickness of the conductive substrate is 200-500nm, preferably 350nm.

[0055] About the electron transport layer:

[0056] The electron transport material includes TiO2, SnO2, ZnO or any other n-type semiconductor material.

[0057] The electron transport material is a nanoparticle with a particle size of 10 to 100 nm; preferably, the particle size is 30 to 50 nm.

[0058] The usage ratio of the electron transport material to the pinene alcohol is 50-200 mg:1 mL, for example, 100 mg:1 mL.

[0059] The dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; specifically, acetylacetone, lauric acid and acetic acid, with a volume ratio of 1:1:2; the volume of the dispersant is 1% to 10% of the volume of terpineol, preferably 4%.

[0060] The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyethylene glycol; specifically, ethyl cellulose and polyethylene glycol; the average molecular weight of the thickener is 5000-20000, preferably 10000; the dosage ratio of the thickener to the pine oil is 50-250 mg:1 mL, such as 150 mg:1 mL.

[0061] The volume of the ethanol is 1 to 3 times, preferably 2 times, the volume of terpineol.

[0062] The method for preparing the electron transport layer slurry comprises the following steps:

[0063] The pine alcohol, dispersant, thickener, ethanol and electron transport material are mixed, and the ethanol is removed by rotary evaporation to obtain an electron transport layer slurry.

[0064] The mixing is at least one of mechanical stirring, ball milling, sand milling, ultrasonic mixing and high shear emulsification; and the mixing time is ≥12h.

[0065] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, preferably 30 rpm; an air pressure of 15 to 50 mbar, preferably 20 mbar; a heating temperature of 45 to 60° C., preferably 50° C.; and a time of 4 to 12 h, preferably 6 h.

[0066] The coating thickness of the electron transport layer slurry is 0.5-2 μm, preferably 0.8 μm.

[0067] The coating method is slit coating, wire rod coating, screen printing or any other slurry coating method.

[0068] The temperature of the heating annealing to form the electron transport layer is 400-600° C., preferably 500° C.; the time is 15-60 minutes, preferably 40 minutes.

[0069] About the insulation layer:

[0070] The insulating layer material includes ZrO2, Al2O3, SiO2 or any other insulating material.

[0071] The insulating layer material is nanoparticles with a particle size of 10 to 100 nm; preferably, the particle size is 30 to 50 nm.

[0072] The usage ratio of the insulating layer material to the pine alcohol is 150-450 mg:1 mL, for example, 250 mg:1 mL.

[0073] The dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; specifically, acetylacetone, lauric acid and acetic acid, with a volume ratio of 1:1:2; the volume of the dispersant is 1% to 10% of the volume of terpineol, preferably 4%.

[0074] The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyethylene glycol; specifically, ethyl cellulose and polyethylene glycol; the average molecular weight of the thickener is 5000-20000, preferably 10000; the dosage ratio of the thickener to the pine oil is 50-250 mg:1 mL, such as 150 mg:1 mL.

[0075] The volume of the ethanol is 1 to 3 times, preferably 2 times, the volume of terpineol.

[0076] The method for preparing the insulating layer slurry comprises the following steps:

[0077] The pine alcohol, dispersant, thickener, ethanol and insulating layer material are mixed, and the ethanol is removed by rotary evaporation to obtain insulating layer slurry.

[0078] The mixing is at least one of mechanical stirring, ball milling, sand milling, ultrasonic mixing and high shear emulsification; and the mixing time is ≥12h.

[0079] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, preferably 30 rpm; an air pressure of 15 to 50 mbar, preferably 20 mbar; a heating temperature of 45 to 60° C., preferably 50° C.; and a time of 4 to 12 h, preferably 6 h.

[0080] The coating thickness of the insulating layer slurry is 1-3 μm, preferably 1.5 μm.

[0081] The coating method is slit coating, wire rod coating, screen printing or any other slurry coating method.

[0082] The temperature for heating to form the insulating layer is 400-600° C., preferably 500° C.; the time is 15-60 minutes, preferably 40 minutes.

[0083] About the protective film:

[0084] The protective material is selected from organic substances that are solid at room temperature and volatile above 300°C; such as at least one of vaseline, paraffin, stearic acid and oleic acid; the vaseline can be white vaseline; preferably, white vaseline and stearic acid are used in a mass ratio of 1:1; or paraffin and oleic acid are used in a mass ratio of 1:1.

[0085] The coating method is slit coating, wire rod coating, screen printing or any other slurry coating method.

[0086] The thickness of the protective film is 0.1-10 μm, preferably 1 μm.

[0087] About Carbon Electrode:

[0088] The carbon material is selected from graphite and conductive carbon black; preferably, graphite with a particle size of 5 to 10 μm (preferably 7 μm) and conductive carbon black with a particle size of 30 to 50 nm (preferably 30 nm) are used in a mass ratio of 4:1.

[0089] The usage ratio of the carbon material to the pine alcohol is 150-450 mg:1 mL, for example, 250 mg:1 mL.

[0090] The dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; specifically, acetylacetone, lauric acid and acetic acid, with a volume ratio of 1:1:2; the volume of the dispersant is 1% to 10% of the volume of terpineol, preferably 4%.

[0091] The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyethylene glycol; specifically, ethyl cellulose and polyethylene glycol; the average molecular weight of the thickener is 5000-20000, preferably 10000; the dosage ratio of the thickener to the pine oil is 50-250 mg:1 mL, such as 150 mg:1 mL.

[0092] The volume of the ethanol is 1 to 3 times, preferably 2 times, the volume of terpineol.

[0093] The preparation method of the carbon slurry comprises the following steps:

[0094] The pine alcohol, dispersant, thickener, ethanol and carbon material are mixed, and the ethanol is removed by rotary evaporation to obtain carbon slurry.

[0095] The mixing is at least one of mechanical stirring, ball milling, sand milling, ultrasonic mixing and high shear emulsification; and the mixing time is ≥12h.

[0096] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, preferably 30 rpm; an air pressure of 15 to 50 mbar, preferably 20 mbar; a heating temperature of 45 to 60° C., preferably 50° C.; and a time of 4 to 12 h, preferably 6 h.

[0097] The coating thickness of the carbon slurry is 10-50 μm, preferably 25 μm.

[0098] The coating method is slit coating, wire rod coating, screen printing or any other slurry coating method.

[0099] The temperature for heating to form the insulating layer is 400-600° C., preferably 500° C.; the time is 15-60 minutes, preferably 40 minutes.

[0100] In step B):

[0101] The perovskite precursor solution is dripped onto the carbon electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing is performed to obtain a device containing perovskite.

[0102] In the perovskite precursor solution, the solvent includes at least one of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO); the solute is ABX3 (wherein A is at least one of methylamine (MA) ion, formamidine (FA) ion and cesium (Cs) ion, and B is Pb 2+ and Sn 2+ At least one of, X is 1 - Br - and Cl - At least one of the following), such as MA 0.4 FA 0.6 In certain embodiments, the solvent comprises DMF and DMSO in a volume ratio of 4:1.

[0103] The concentration of the perovskite precursor solution is 1.0-1.5 mol / L, preferably 1.2 mol / L.

[0104] The amount of the perovskite precursor solution added to the blank device is 2-4 μL / cm 2 , preferably 3 μL / cm 2 .

[0105] The annealing temperature is 60-120°C, and the time is 4-24h; preferably, when the annealing temperature is 60°C / 80°C / 100°C / 120°C, the corresponding time is 24h / 16h / 8h / 4h. The annealing is used to remove the solvent in the perovskite precursor solution and precipitate the perovskite.

[0106] In step C):

[0107] A back plate is added to the bottom electrode of the device obtained in step B), wires are connected, and sealant is applied to obtain a mesoporous perovskite solar cell.

[0108] The back panel is made of glass, organic glass or other airtight panels.

[0109] The present invention has no particular limitation on the method of connecting the wires, and any method of connecting the wires well known to those skilled in the art may be used.

[0110] The sealant can be commercial sealant, and common ingredients include epoxy resin or ethylene-vinyl acetate copolymer.

[0111] Figure 1 : is a comparison diagram of the coating method of the present invention and the conventional perovskite solar cell. Figure 1It can be seen that the traditional coating process is to coat the carbon electrode slurry on the ZrO2 insulating layer, which will cause the carbon slurry to dissolve and penetrate the ZrO2 insulating layer, resulting in device short circuit and reduced efficiency; the core point of the method adopted by the present invention is that a protective layer is pre-coated on the surface of the ZrO2 insulating layer. The carbon electrode cannot dissolve or corrode the ZrO2 insulating layer during coating, preventing the device from short circuiting, thereby improving the device efficiency.

[0112] Beneficial effects:

[0113] 1) The present invention can effectively prevent battery short circuit: due to the presence of a protective film between the insulating layer and the carbon slurry, the carbon slurry cannot completely corrode the protective film before drying, thereby preventing the carbon slurry from penetrating the insulating layer and contacting the electron transport layer, thereby preventing the device from short circuiting.

[0114] 2) The process is simple, the equipment cost is low, the production process is mild, the risk is low and it is easy to operate.

[0115] 3) Low cost: The main raw materials used, such as vaseline, paraffin, stearic acid, etc., are all commonly used cheap chemical raw materials. No high-priced raw materials or equipment are required, which reduces costs.

[0116] 4) High device performance: The device obtained by the present invention does not have an internal short circuit, which reduces leakage loss, thereby ensuring the photoelectric conversion efficiency of the solar cell.

[0117] 5) It is conducive to large-scale production: large-area perovskite solar cells are more sensitive to short-circuit problems. The present invention greatly reduces the risk of short circuits in the battery, which is conducive to the manufacture of large-area perovskite solar cells.

[0118] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.

[0119] In order to further illustrate the present invention, a perovskite solar cell and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but it should not be construed as limiting the protection scope of the present invention.

[0120] Example 1

[0121] 1) Preparation of electron transport layer slurry:

[0122] Use 20 mL of pineol, 40 mL of ethanol, 0.2 mL of acetylacetone, 0.4 mL of acetic acid and 0.2 mL of lauric acid respectively, 2 g of ethyl cellulose (average molecular weight 10,000) and 1 g of polyethylene glycol (average molecular weight 10,000) respectively, 2 g of TiO2 with a particle size of 30-50 nm, and perform high shear emulsification for 1 h (speed 6,000 rpm), ball milling for 24 h (speed 300 rpm), ultrasound for 1 h, and rotary evaporation at 45 ° C for 6 h (pressure 20 mbar) to remove ethanol to obtain an electron transport layer slurry.

[0123] 2) Preparation of insulation layer slurry:

[0124] Use 20 mL of pineol, 40 mL of ethanol, 0.2 mL, 0.4 mL, 0.2 mL of acetylacetone, acetic acid and lauric acid respectively, 2 g, 1 g of ethyl cellulose (average molecular weight 10,000) and polyethylene glycol (average molecular weight 10,000), 5 g of ZrO2 with a particle size of 30-50 nm, and perform high shear emulsification for 1 h (speed 6,000 rpm), ball milling for 24 h (speed 300 rpm), ultrasound for 1 h, and rotary evaporation at 45 ° C for 6 h (pressure 20 mbar) to remove ethanol to obtain an insulating layer slurry.

[0125] 3) Preparation of carbon slurry:

[0126] Use 20mL of pineol, 40mL of ethanol, 0.2mL, 0.4mL, 0.2mL of acetylacetone, acetic acid and lauric acid respectively, 2g and 1g of ethyl cellulose (average molecular weight 10000) and polyethylene glycol (average molecular weight 10000), 4g and 1g of 7μm graphite and 30nm conductive carbon black respectively, high shear emulsification for 1h (speed 6000rpm), ball milling for 24h (speed 300rpm), ultrasound for 1h, and rotary evaporation at 45℃ for 6h (pressure 20mbar) to remove ethanol to make a carbon slurry.

[0127] 4) coating the electron transport layer slurry on the conductive substrate with a coating thickness of 0.8 μm, and heating at 500°C for 40 min to form an electron transport layer; coating the insulating layer slurry on the electron transport layer with a coating thickness of 1500 nm (1.5 μm), and heating at 500°C for 40 min to form an insulating layer; then coating the protective material (white vaseline and stearic acid, mass ratio of 1:1) on the insulating layer, and obtaining a protective film with a thickness of 1 μm after curing; then coating the carbon slurry on the protective film with a coating thickness of 40 μm, and then heating at 400°C for 40 min to form a carbon electrode and volatilize the protective film to obtain a blank device without perovskite;

[0128] 5) The perovskite precursor solution (solvent includes DMF and DMSO, volume ratio is 4:1; solute is MA 0.4 FA 0.6 PbI3, concentration of 1.2 mol / L) was added dropwise onto the bottom electrode of the blank device (addition volume was 3 μL / cm 2 ), after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing is performed at 80°C for 16h to obtain a perovskite-containing device.

[0129] 6) A back plate is added to the bottom electrode of the device obtained in step 5), a wire is connected, and a sealant is applied to obtain a mesoporous perovskite solar cell.

[0130] Example 2

[0131] The difference from Example 1 is:

[0132] In step 4): the thickness of the protective film is 5 μm.

[0133] The other steps are the same as those in Example 1 to obtain a mesoporous perovskite solar cell.

[0134] Example 3

[0135] The difference from Example 1 is:

[0136] In step 4), the protective material is paraffin and oleic acid, with a mass ratio of 1:1.

[0137] The other steps are the same as those in Example 1 to obtain a mesoporous perovskite solar cell.

[0138] Comparative Example

[0139] The difference from Example 1 is:

[0140] In step 4), the carbon slurry is directly coated on the insulating layer without providing a protective film.

[0141] The other steps are the same as those in Example 1 to obtain a mesoporous perovskite solar cell.

[0142] Figure 2 The IV test curves of the mesoporous perovskite solar cells obtained in Examples 1 to 3 of the present invention and the comparative example. The IV test uses a steady-state solar light source, the test scan range is 1V to 0V, and a reverse scan is used with a scan rate of 50mV / s. Figure 2 It can be seen that the voltage and current of the three embodiments are significantly higher than those of the comparative example.

[0143] The electrical properties of the mesoporous perovskite solar cells obtained in Examples 1 to 3 of the present invention and the comparative example were tested, and the results are shown in Table 1. The test conditions are the same as Figure 2 .

[0144] Table 1 Electrical performance test results of mesoporous perovskite solar cells obtained in Examples 1 to 3 and Comparative Examples

[0145]

[0146]

[0147] As can be seen from Table 1, after adopting the coating method of adding a protective layer of the present invention, the leakage resistance of the device increases by about 2 orders of magnitude, suppressing the leakage loss of the device, thereby improving the voltage and current of the device, and finally improving the photoelectric conversion efficiency of the device by about 5 to 9 percentage points. It can be seen that the voltage, current and conversion efficiency of the embodiment are all higher than those of the comparative example.

[0148] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a perovskite solar cell, comprising the following steps: A) coating the electron transport layer slurry on a conductive substrate, heating and annealing to form an electron transport layer; The insulating layer slurry is coated on the electron transport layer and dried to form an insulating layer; the protective material is then coated on the insulating layer and cured to obtain a protective film; the carbon slurry is then coated on the protective film, heated and annealed to form a carbon electrode and the protective film is volatilized to obtain a blank device without perovskite; The raw materials for preparing the electron transport layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an electron transport material; the raw materials for preparing the insulating layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an insulating layer material; the raw materials for preparing the carbon slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and a carbon material; B) dropping a perovskite precursor solution onto the carbon electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing to obtain a perovskite-containing device; C) Covering the bottom electrode of the device obtained in step B) with a back plate, connecting wires, and applying sealant to obtain a mesoporous perovskite solar cell.

2. The preparation method according to claim 1, characterized in that: The protective material is selected from at least one of vaseline, paraffin, stearic acid and oleic acid.

3. The preparation method according to claim 1, characterized in that: The dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; the volume of the dispersant is 1% to 10% of the volume of terpineol; The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyethylene glycol; the dosage ratio of the thickener to the terpineol is 50-250 mg: 1 mL; The volume of the ethanol is 1 to 3 times the volume of terpineol.

4. The preparation method according to claim 1, characterized in that: The electron transport material includes TiO2, SnO2 or ZnO; The electron transport material is a nanoparticle with a particle size of 10 to 100 nm; In the raw materials for preparing the electron transport layer slurry, the usage ratio of the electron transport material to the pinene alcohol is 50-200 mg:1 mL.

5. The preparation method according to claim 1, characterized in that: The method for preparing the electron transport layer slurry comprises the following steps: Mixing pinene alcohol, a dispersant, a thickener, ethanol and an electron transport material, and removing the ethanol by rotary evaporation to obtain an electron transport layer slurry; The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 45 to 60° C., and a heating time of 4 to 12 hours.

6. The preparation method according to claim 1, characterized in that: The insulating layer material includes ZrO2, Al2O3 or SiO2; The insulating layer material is nanoparticles with a particle size of 10 to 100 nm; In the raw materials for preparing the insulating layer slurry, the usage ratio of the insulating layer material to the pinene alcohol is 150-450 mg:1 mL; The method for preparing the insulating layer slurry comprises the following steps: Mixing pineol, a dispersant, a thickener, ethanol and an insulating layer material, and removing the ethanol by rotary evaporation to obtain an insulating layer slurry; The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 45 to 60° C., and a heating time of 4 to 12 hours.

7. The preparation method according to claim 1, characterized in that: The carbon material is selected from graphite and conductive carbon black; The usage ratio of the carbon material to the pine alcohol is 150-450 mg:1 mL; The preparation method of the carbon slurry comprises the following steps: Mixing terpineol, a dispersant, a thickener, ethanol and a carbon material, and removing the ethanol by rotary evaporation to obtain a carbon slurry; The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 45 to 60° C., and a heating time of 4 to 12 hours.

8. The preparation method according to claim 1, characterized in that: The coating thickness of the electron transport layer slurry is 0.5 to 2 μm; The coating thickness of the insulating layer slurry is 1 to 3 μm; The thickness of the protective film is 0.1 to 10 μm; The coating thickness of the carbon slurry is 10 to 50 μm.

9. The preparation method according to claim 1, characterized in that: In step B), the perovskite precursor solution comprises a solvent including at least one of dimethylformamide and dimethyl sulfoxide; the solute is ABX3; wherein A is at least one of methylamine ion, formamidine ion and cesium ion, and B is Pb 2+ and Sn 2+ At least one of, X is 1 - Br - and Cl - At least one of; The concentration of the perovskite precursor solution is 1.0 to 1.5 mol / L; The amount of the perovskite precursor solution added to the blank device is 2-4 μL / cm 2 ; The annealing temperature is 60-120° C. and the annealing time is 4-24 hours.

10. A perovskite solar cell prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Perovskite solar cell and carbon slurry and preparation method thereof

    CN115064301A

  • Efficient stable perovskite battery comprising permeation-proof carbon film and preparation method thereof

    CN106252515A

  • Cheap stable perovskite solar energy cell and driven photocatalytic device

    CN108258120A

  • Perovskite cell preparation method and perovskite cell

    CN116669500A

  • Carbon-based perovskite solar cell based on aluminum oxide / carbon material double-mesoporous layer and preparation method of carbon-based perovskite solar cell

    CN118317672A